Placental transmogrification of the lung: A case report with computed tomography–pathologic correlation - Ayumi Kamei, MD; Yasunari Yamada, MD; Hiroshi Baba, MD; Hiroshi Mizuuchi, MD; Noriaki Yamamoto, MD; Hidenori Kouso, MD; Kensaku Ito, MD; Takaaki Mori, MD; Takeaki Dotsu, MD; Hajime Takaki, MD; Yoshiki Asayama, MD (Radiology Case Reports)
We herein present a case involving a 62-year-old woman with a 1-month history of persistent dry cough. A thoracic computed tomography scan revealed multiple cystic lesions with well-defined thin septal thickening, tiny nodules, and areas of irregular consolidation characterized by irregular septal thickening in the right lower lobe. This thickening formed pentagonal and hexagonal patterns resembling a soccer ball. A ground-glass nodule was observed in a different area of the anterior basal segment of the right lung (S8) and was suspected to be adenocarcinoma in situ. This diagnosis was confirmed, along with placental transmogrification of the lung, after the patient underwent right lower lobectomy via video-assisted thoracoscopic surgery. Irregular septal thickening with pentagonal and hexagonal patterns resembling a soccer ball may suggest placental transmogrification of the lung in patients with multiple cystic lesions in a unilateral lung.